Groundwork for the development of the Brazilian Portuguese wordnet - Dias-Da-Silva, Bento C. [UNESP]; De Oliveira, Mirna F. [UNESP]; De Moraes, Helio R. [UNESP] (Springer Nature, 2002)
Considering the Princeton WordNet built for English as a reference, new Wordnets in other languages are being built, such as the ones for European Portuguese, Galician, Basque, Catalan, and Spanish, just to mention some Iberian languages. In this paper we set the groundwork for the development of the Brazilian Portuguese Wordnet: the compilation of a WordNet-based Brazilian Portuguese Thesaurus, a particular dictionary of synonyms and antonyms stored in a computer for use in word processing. As there were no available machine tractable wide range lexical resources whatsoever for Brazilian Portuguese, and strict manual construction of lexicons from scratch is costly and highly time-consuming, we have focused on the massive acquisition and filtering of lexical knowledge and semantic information from pre-existing structured lexical resources. Accordingly, in this paper we present the methodology we used, the lexical resources we employed, and the computing tools we designed to develop such a thesaurus from conventional dictionaries available for Brazilian Portuguese.